ASSESSMENT OF SEROLOGICAL VALUES OF NT-PRO BNP LEVELS IN CLINICALLY STABLE POST COVID PATIENTS IN THE DURATION OF 1 ½ YEAR TO 2 YEARS AFTER EXPOSURE TO COVID-19 INFECTION - Dr. Harshvardhan Prakash Kanase, Dr. Umesh Vamanrao Tekawade, Dr. Rupesh Kadam, Dr.Suvarna Shelar, Dr.Sachin Patil, Dr.Umesh Ghate, Dr. Goutam Jadeja (Chelonian Research Foundation, 2023)
study was carried out in 36 patients of 3 different groups regarding assessment of serological levels of NT proBNP. The test was carried out in three groups of patients. Group A : 12 patients of mild catergory, Group B : 12 patients of moderate category, Group C : 12 patients of severe category. The values we obtained after doing NT proBNP test were compared. It was observed that the values were raised in patients who required O2 support during covid 19 infection. Values in old patients and female patients are higher than the young patients and male patients. Keywords: NT proBNP, COVID-19, SARS-CoV-2, DEATH.